Pinpointing the position of flying songbirds with a wireless microphone array: three-dimensional triangulation of warblers on the wing. Issue 4 (3rd July 2020) - Gayk, Zach G.; Mennill, Daniel J.
ABSTRACT: Flight calls, the quiet calls emitted by migratory birds on the wing, offer opportunities to understand the behaviour of birds during migration. We test the effectiveness of an eight-element microphone array for three-dimensional triangulation of the position of calling migratory birds. We constructed a microphone array out of commercially available components and used freely available software to process the recordings, so that this technology might be easily adopted for migration monitoring. In the Great Lakes region of North America, we triangulated the position of loudspeakers broadcasting synthetic tones and flight calls, as well as calls of actual passing migrants. Loudspeakers broadcasting synthetic tones showed a triangulation accuracy of 1.52 ± 0.34 m. Loudspeakers broadcasting flight calls of migratory wood-warblers showed a triangulation accuracy of 2.04 ± 0.37 m. Actual migratory warblers passing over the microphone array showed an estimated accuracy of 2.70 ± 0.48 m. We conclude that wireless microphone arrays accurately triangulate migrant birds, at least under optimal recording conditions. We present this proof-of-concept study to demonstrate the reliability of this underutilized technique which should be of interest as a tool for studying migratory bird behaviour, for quantifying migratory bird populations, and for monitoring the conservation of migratory birds.